Analyzing Profil Pelajar Pancasila Values in Elementary School Textbook - Permana, Dio Resta; Agusta, Okky Leo (Linguists : Journal of Linguistics and Language Teaching, 2023)
This study aimed at investigating Profil Pelajar Pancasila Values in English textbooks “My Next Words” for elementary school students of Merdeka Curriculum. This analysis was really needed to explore the character education material proposed in the Merdeka Curriculum to form elementary students with noble values. A content analysis technique was employed in this current study. The result of the study showed that the existence of Profil Pelajar Pancasila values related to Critical Reasoning as the most frequent occurrence category. Then, there were character values related to Having Faith, Fearing God, Having Character and Being Independent. In internalizing Profil Pelajar Pancasila Values, teachers must be active in making integration character values from texts and pictures in the textbook with their lesson plan. These findings lead to the conclusion that the upcoming textbooks should pay attention in the distribution of character values and the role of the teachers in teaching the characters should be maximized.